Diaspora’s homeland : modern China in the age of global migration - van Dongen, Els (2021)
In a 2004 lecture entitled “Why China Historians Should Study the Chinese Diaspora, and Vice-versa,” the renowned historian Philip A. Kuhn made the case for the intermingled processes of modern Chinese history and the history of Chinese emigration. Continuing these efforts of cross-fertilization by Philip A. Kuhn and, among others, Madeline Y. Hsu, Adam M. McKeown, and Glen Peterson, in Diaspora’s Homeland, Shelly Chan puts in dialogue the fields of overseas Chinese, Chinese American, and modern Chinese history. Unlike in other accounts, however, the book’s starting point is the overlooked question: “How did it change China?” (1). This question goes beyond earlier approaches that Chan characterizes as “the sum of parts,” namely mapping distributions of Chinese in “fixed” countries and regions, or “interactions between parts,” namely outlining transnational connections at various levels (7-8). Instead, the book is preoccupied with the emigrants’ influence on China and how diaspora-homeland dynamics transformed China into an invented permanent “homeland.”